2009
DOI: 10.1098/rsbl.2009.0076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of food on bacterial community composition associated with the copepod Acartia tonsa Dana

Abstract: The estuarine copepod Acartia tonsa naturally carried diverse strains of bacteria on its body. The bacterial community composition (BCC) remained very conservative even when the copepod was fed different axenic algal species, indicating that the food per se did not much affect BCC associated with the copepod. In xenic algal treatments, however, copepod-associated BCC differed with each alga fed, even though the same bacterial source was used to inoculate the alga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 26 publications
3
46
0
Order By: Relevance
“…(4) Several phylotypes are related with chitindegrading bacteria. Tang et al (2009a) postulated that the life strategies of the different copepod genera with regard to feeding strategies play an important role for the composition of the associated bacterial communities. Interestingly, we could not support their hypothesis, since the different copepod genera investigated in this study display different life styles (herbivorous, omnivorous or detrivorous), but did not show significant differences in their bacterial community in respect to DGGE patterns.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Several phylotypes are related with chitindegrading bacteria. Tang et al (2009a) postulated that the life strategies of the different copepod genera with regard to feeding strategies play an important role for the composition of the associated bacterial communities. Interestingly, we could not support their hypothesis, since the different copepod genera investigated in this study display different life styles (herbivorous, omnivorous or detrivorous), but did not show significant differences in their bacterial community in respect to DGGE patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Methods used to quantify bacteria are also included (Table continued on next page) Alpha-, Beta-, and Gammaproteobacteria). Using the same technique, Tang et al (2009b) identified 37 discrete phylogenetic units from the marine copepod Acartia tonsa that belonged to 3 major bacteria groups (Alpha-and Gammaproteobacteria, Bacteroidetes). Surprisingly, Møller et al (2007) found only 3 different Roseobacter species on Calanus spp.…”
Section: ± 210mentioning
confidence: 99%
“…When the copepod Acartia tonsa was feeding on different axenic phytoplankton diets, the bacterial diversity associated with the copepod decreased and converged, indicating the presence of a rather stable resident bacterial community (Tang et al 2009b). In contrast, the bacterial diversity greatly diverged and several species such as Pseudoalteromonas, Sulfitobacter, and Roseobacter only appeared when the copepod was feeding on xenic phytoplankton diets, indicating that many of the transient bacteria either actively attached to the animal's body surfaces or were passively ingested (Tang et al 2009b). Similarly, in a field study, Grossart et al (2009) observed that the bacterial diversity associated with freshwater zooplankton (Thermocyclops oithonoides and Bosmina coregoni) decreased after gut evacuation.…”
Section: ± 210mentioning
confidence: 99%
“…Often the first line of defense for many groups of invertebrates, the hard, chitinous exoskeleton provides a physical and chemical barrier against pathogen attachment and invasion (78,79). A potentially vulnerable point of entry into the host, the gut is lined with the peritrophic matrix, which acts like a sieve that surrounds and prevents bacteria, bacterial toxins, and hard food fragments from contacting the intestinal epithelium (11,(80)(81)(82). When the thickness and permeability of the peritrophic matrix is compromised in Drosophila, there is higher susceptibility to infection by pathogenic bacteria or mortality from bacterial toxins (83).…”
Section: Host Regulation Of the Microbiomementioning
confidence: 99%